PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN MANAJEMEN KEUANGAN TERHADAP MINAT MEMULAI USAHA PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN KERINCI - Rezki Agrisa Ditama (LPPM - STIE SAKTI ALAM KERINCI, 2022)
This study aims to determine the effect of Entrepreneurial Knowledge of Entrepreneurship and Financial Management, either simultaneously or partially on the interest in starting a business for students of the Islamic Economics and Business Faculty IAIN Kerinci. This type of research is descriptive quantitative research. The population in this study were students of the Faculty of Economics and Islamic Business IAIN Kerinci majoring in Islamic Banking and Islamic Economics class of 2018 and 2019. The sample was determined using a cluster random sampling technique, so that the respondents of this study were 82 students. Data collection techniques using a questionnaire. As for the data analysis technique in this study using multiple linear regression analysis with the help of the program SPSS version 23. The results showed that both partially and simultaneously entrepreneurial knowledge of entrepreneurship and financial management had a significant effect on the interest in starting a business for students of the Faculty of Economics and Islamic Business IAIN Kerinci.